Past and present experience shifts audiovisual temporal perception in rats - Al-youzbaki, Mohammed U.; Schormans, Ashley L.; Allman, Brian L. (Frontiers in Behavioral Neuroscience, 2023)
Our brains have a propensity to integrate closely-timed auditory and visual stimuli into a unified percept; a phenomenon that is highly malleable based on prior sensory experiences, and is known to be altered in clinical populations. While the neural correlates of audiovisual temporal perception have been investigated using neuroimaging and electroencephalography techniques in humans, animal research will be required to uncover the underlying cellular and molecular mechanisms. Prior to conducting such mechanistic studies, it is important to first confirm the translational potential of any prospective animal model. Thus, in the present study, we conducted a series of experiments to determine if rats show the hallmarks of audiovisual temporal perception observed in neurotypical humans, and whether the rat behavioral paradigms could reveal when they experienced perceptual disruptions akin to those observed in neurodevelopmental disorders. After training rats to perform a temporal order judgment (TOJ) or synchrony judgment (SJ) task, we found that the rats’ perception was malleable based on their past and present sensory experiences. More specifically, passive exposure to asynchronous audiovisual stimulation in the minutes prior to behavioral testing caused the rats’ perception to predictably shift in the direction of the leading stimulus; findings which represent the first time that this form of audiovisual perceptual malleability has been reported in non-human subjects. Furthermore, rats performing the TOJ task also showed evidence of rapid recalibration, in which their audiovisual temporal perception on the current trial was predictably influenced by the timing lag between the auditory and visual stimuli in the preceding trial. Finally, by manipulating either experimental testing parameters or altering the rats’ neurochemistry with a systemic injection of MK-801, we showed that the TOJ and SJ tasks could identify when the rats had difficulty judging the timing of audiovisual stimuli. These findings confirm that the behavioral paradigms are indeed suitable for future testing of rats with perceptual disruptions in audiovisual processing. Overall, our collective results highlight that rats represent an excellent animal model to study the cellular and molecular mechanisms underlying the acuity and malleability of audiovisual temporal perception, as they showcase the perceptual hallmarks commonly observed in humans.